Education: Honesty, Discipline, Patience, and Ethics as Media in Implementing Government Financial Accounting in Samarinda, Indonesia - La Ode Hasiara; Ida Bagus Putu Suamba (Soshum: Jurnal Sosial dan Humaniora, 2020)
Social networking media has been the major source of communication The aim of the research is to understand the meaning of education, honesty, discipline, and patience for better implementation of regional government financial accounting. The research uses descriptive qualitative method, which is a research that results in descriptive data in form of words from key informants observed based on their experience. Quantitative research is an inductive approach based on the real condition, a knowledge that emphasize on the field actual condition based on the experience of each individual informant. The research result indicates that education, honesty, discipline and patience are the key in the implementation of regional government financial accounting since the four components are an intact unity. It can be concluded that the four components are inseparable thus they are the media in the implementation of regional government financial accounting in Indonesia